Plague During Pregnancy: A Systematic Review. (21st May 2020) - Fleck-Derderian, Shannon; Nelson, Christina A; Cooley, Katharine M; Russell, Zachary; Godfred-Cato, Shana; Oussayef, Nadia L; Oduyebo, Titilope; Rasmussen, Sonja A; Jamieson, Denise J; Meaney-Delman, Dana
Abstract: Background: Yersinia pestis continues to cause sporadic cases and outbreaks of plague worldwide and is considered a tier 1 bioterrorism select agent due to its potential for intentional use. Knowledge about the clinical manifestations of plague during pregnancy, specifically the maternal, fetal, and neonatal risks, is very limited. Methods: We searched 12 literature databases, performed hand searches, and consulted plague experts to identify publications on plague during pregnancy. Articles were included if they reported a case of plague during pregnancy and at least 1 maternal or fetal outcome. Results: Our search identified 6425 articles, of which 59 were eligible for inclusion and described 160 cases of plague among pregnant women. Most published cases occurred during the preantibiotic era. Among those treated with antimicrobials, the most commonly used were sulfonamides (75%) and streptomycin (54%). Among cases treated with antimicrobials, maternal mortality and fetal fatality were 29% and 62%, respectively; for untreated cases, maternal mortality and fetal fatality were 67% and 74%, respectively. Five cases demonstrated evidence of Y. pestis in fetal or neonatal tissues. Conclusions: Untreated Y. pestis infection during pregnancy is associated with a high risk of maternal mortality and pregnancy loss. Appropriate antimicrobial treatment can improve maternal survival, although even with antimicrobial treatment, there remains a high risk of pregnancy loss. Limited evidence suggests that maternal-fetal transmission of Y. pestis is possible, particularly in the absence of antimicrobial treatment. These results emphasize the need to treat or prophylax pregnant women with suspected plague with highly effective antimicrobials as quickly as possible. Abstract : Untreated Yersinia pestis infection during pregnancy is associated with high maternal mortality, pregnancy complications, fetal loss, and neonatal death. Appropriate antimicrobial treatment can improve maternal survival, although even with antimicrobial treatment, the risk of maternal death and pregnancy loss remains.